2022
DOI: 10.1080/21623945.2022.2065715
|View full text |Cite
|
Sign up to set email alerts
|

Myostatin increases the expression of matrix metalloproteinase genes to promote preadipocytes differentiation in pigs

Abstract: ABSTACT Myostatin (MSTN) resulted in reduced backfat thickness in MSTN-knockout (MSTN-KO) pigs, whereas the underlying mechanism remains elusive. In this study, RNA sequencing (RNA-seq) was used to screen differentially expressed genes (DEGs) in porcine fat tissues. We identified 285 DEGs, including 4 adipocyte differentiation-related genes (ADRGs). Matrix Metalloproteinase-2/7 (MMP-2/7), fibronectin (FN), and laminin (LN) were differentially expressed in MSTN-KO pigs compared with wild-type (WT) pi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…RNAi was applied to investigate the porcine MSTN gene. However, to the best of our knowledge, no MSTN knockdown pigs were generated using this approach. ZNFs were applied to target the porcine MSTN in somatic cells , and to generate live ZFNs-mediated MSTN -edited pigs (Table ).…”
Section: Targeting the Mstn Gene In Pigsmentioning
confidence: 99%
See 2 more Smart Citations
“…RNAi was applied to investigate the porcine MSTN gene. However, to the best of our knowledge, no MSTN knockdown pigs were generated using this approach. ZNFs were applied to target the porcine MSTN in somatic cells , and to generate live ZFNs-mediated MSTN -edited pigs (Table ).…”
Section: Targeting the Mstn Gene In Pigsmentioning
confidence: 99%
“…It was also shown that MSTN has a functional partition to coordinate both adipogenesis and myogenesis, and MSTN acts through the MEF2C /miR222/ SCD5 cascade to regulate fatty acid metabolism . Furthermore, MSTN was shown to increase the expression of matrix metalloproteinase genes to promote preadipocyte differentiation …”
Section: Targeting the Mstn Gene In Pigsmentioning
confidence: 99%
See 1 more Smart Citation